Association between the Angle of the Left Subclavian Artery and Procedural Time for Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome. (17th November 2022) - Miyagawa, Masatsugu; Fukamachi, Daisuke; Fukumoto, Katsunori; Monden, Masaki; Takahashi, Kurara; Migita, Shohei; Mizobuchi, Saki; Tanaka, Yudai; Ogaku, Akihito; Koyama, Yutaka; Fujito, Hidesato; Arai, Riku; et al.
Abstract : Background . The effect of left subclavian artery tortuosity during percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS) remains unclear. Methods . Of 245 ACS patients (from November 2019 and May 2021), 79 who underwent PCI via a left radial approach (LRA) were included. We measured the angle of the left subclavian artery in the coronal view on CT imaging as an indicator of the tortuosity and investigated the association between that angle and the clinical variables and procedural time. Results . Patients with a left subclavian artery angle of a median of <70 degrees (severe tortuosity) were older (75.4 ± 11.7 vs. 62.9 ± 12.3 years, P < 0.001 ) and had a higher prevalence of female sex (42.1% vs. 14.6%, P = 0.007 ), hypertension (94.7% vs. 75.6%, P = 0.02 ), and subclavian artery calcification (73.7% vs. 34.2%, P < 0.001 ) than those with that ≥70 degrees. The left subclavian artery angle correlated negatively with the sheath cannulation to the first balloon time ( ρ  = −0.51, P < 0.001 ) and total procedural time ( ρ  = −0.32, P = 0.004 ). A multiple linear regression analysis revealed that the natural log transformation of the sheath insertion to first balloon time was associated with a subclavian artery angle of <70 degrees ( β  = 0.45, P < 0.001 ). Conclusion . Our study showed that lower left subclavian artery angles as a marker of the tortuosity via the LRA were strongly associated with a longer sheath insertion to balloon time and subsequent entire procedure time during the PCI.